Commitment in first-price auctions - Philippe Gillen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We study the role of commitment in a first-price auction environment. We devise a simple two-stage model in which bidders first submit an initial offer that the auctioneer can observe and then make a counteroffer. There is no commitment on the auctioneer's side to accept an offer as is or even to choose the lowest bidder. We compare this setting to a standard first-price auction both theoretically and experimentally. While theory suggests that the offers and the auctioneer's revenue should be higher in a standard first-price auction compared to the first-price auction with renegotiation, we cannot confirm these hypotheses in the experiment.
Keywords: D44; D47; 330; Auctions; Experiment